Different Types of Needles for Specific Uses? Experimental Reproductions of some Finds from Aradetis Orgora, Georgia - Sara Maria Stellacci (EXARC Journal)
This research aimed to evaluate some new hypotheses about the production and use of a class of pointed tools from the Bronze Age layers of Aradetis Orgora (Georgia), which have been traditionally considered as pins. Its main goal was to provide an alternative interpretation of their function, namely as tools used in basketry. The study was divided into two experimental steps. The first step of the experimental protocol was the construction of replicas of the ancient artefacts for which techniques and tools, similar to those employed in ancient times, were used. As a second step, different sewing techniques on different materials (various types of plants and leather) were reproduced with the help of an expert craftsperson. Experimental reproduction, together with the preliminary comparison between the experimental traces and the archaeological ones, not only helped to understand how these specific needles were used (the gestures used with the needle on a specific material), but also to highlight the craft activities carried out within the site during the Bronze Age.